PENETAPAN KADAR ASAM BENZOAT DALAM BEBERAPA MERK DAGANG MINUMAN RINGAN SECARA SPEKTROFOTOMETRI ULTRAVIOLET - Wahyu Irna Wati; Any Guntarti (Pharmaciana, 2012)
Benzoic acid is one of the synthetic preservatives, work effectively at pH 2.5 to4.0, therefore it is widely used in acidic food or drink. This study aims to determinebenzoic acid content in some soft drink products, their conformity with Permenkes RINo.722/Menkes/Per/IX/88 on food additives, and to find out if there were any varianceof benzoid acid content in a different kinds of soft drink products.Determination of benzoid acid levels was performed by ultravioletspectrophotometry following solvent extraction of the benzoid acid with chloroform.Qualitatively, it was found that all of the sample contained benzoid acid. Quantitatively,the amount of benzoid acid in sample A was 227,73 mg/kg of materials; sample B was182,38 mg/kg of materials; sampel C was 259,52 mg/kg of materials; sample D was325,01 mg/kg of materials; sample E was 357,33 mg/kg of material. The resultindicated that there were variance of benzoid acid content in different soft drinkproducts. The use of benzoic acid in soft drinks was lower compaired to that ofPermenkes RI No.722/Menkes/Per/IX/88 (600 mg/kg of materials).